Morfologia, conservação e ecofisiologia da germinação de sementes de Psidium cattleianum Sabine - Silva, Antonio da (Universidade Federal de São Carlos, 2009)
Psidium cattleianum has great potential for animal and human food, for multiple uses of wood and for recovery of degraded areas. Due to its economic importance and to the lack of information on seed germination and conservation, this study aimed to find the morphology of fruits, seeds, seedlings and young plants and to establish the presence or absence of dormancy. Furthermore, studies have been conducted relating to the conservation of seeds, the germination responses under different temperatures, qualities of light and humidity levels of the substrates. All these studies focus to generate knowledge that can help to support conservation projects, management and restoration of altered and/or protected areas. By the results, it was found that seeds and fruits showed had little biometric variation and the greatest variation occured in number of seeds per fruit. The seeds showed tegumentary dormancy, the germination is hypogeal and the seedlings are cryptocotylar. Seeds immersed in water at room temperature in laboratory, proved germination pending quicker 20- 30oC in white light. The seed immersed in sulfuric acid during ten, 20 and 25 minutes, subjected to temperatures of 20-30oC under white light, showed higher germination rate. The placing of the seeds in waterproof packed and stored in natural environment in the laboratory or in a dry chamber, as well as the seeds packed in semi-permeable package and stored in cold chamber, were suitable for the preservation during 1,107 days and this fact, associated with little variation on the moisture content allowed to classify them as orthodoxe ones. The test of electrical conductivity with scarified seeds in the sulfuric acid during 25 minutes was not efficient to evaluate its physiological quality. The highest values of seed germination and speed rate were obtained at the temperature of 20-30oC under white light. Regardless of temperatures, the seeds showed drastic reduction in speed and germination in absence and presence of far red light. The seeds are positive preferential photoblastic. It is assumed that seeds germination is better under light natural conditions. The highest values of seed speed and germination were obtained, under white light regardless of seed age. The highest seed speed and germination were obtained at 20-30oC, under white light in 15 mL of water, as well as 50 grams of sand moistened with six, nine and 12 mL of water.
MORPHOLOGY, CONSERVATION AND ECOPHYSIOLOGY OF Psidium cattleianum Sabine SEED GERMINATION
Keywords: Semente florestal; Dormência; Armazenamento; Temperatura; Luz; Substrato; Forest seed; Dormancy; Storage; Light; Substrate; CIENCIAS BIOLOGICAS::ECOLOGIA